Microprocessor based hardware-software complex for investigating the magnetic surfaces of torsatron URAGAN-2M - Gubarev, S.P.; Lesnyakov, G.G.; Opaleva, G.P.; Shapoval, A.N.; Taran, V.S.; Zolototrubova, M.I. (Вопросы атомной науки и техники, 2012)
This paper describes the microprocessor hardware and software complex designed to control the fluorescent rod scanning in the poloidal cross section of vacuum toroidal chamber in order to study the structure of magnetic surfacesin the torsatron "URAGAN-2M."